Vitamin D Receptor (VDR) TaqI Gene Polymorphisms as Profiling Markers for Cardiovascular Disease - Negi, Neha; Ahmad, Yusra; Parveen, Hiba; Shaji, Jasna; Sharma, Narotam; Singh, Ankita (Journal of Neonatal Surgery, 2025)
Cardiovascular diseases (CVDs) continue to be a major worldwide health problem, and they are increasingly being linked to genetic vulnerability in addition to traditional risk factors. Because it affects calcium-phosphorus balance, immunological regulation, and vascular function, the Vitamin D Receptor (VDR) gene—specifically, its TaqI polymorphism (rs731236)—has been identified as a significant modulator among the genes determining CVD risk. The biological relevance of vitamin D metabolism, the genetic makeup of the VDR gene, and the clinical consequences of its variants in relation to cardiovascular health are all examined in this study. Particular attention is paid to the people of the Dehradun area, where environmental variables like as dietary habits and varying amounts of sunshine exposure may influence the expression and consequences of VDR polymorphisms.